ChemInform Abstract: Ruthenium‐Catalyzed Intermolecular Hydroacylation of Internal Alkynes: The Use of Ceria‐Supported Catalyst Facilitates the Catalyst Recycling. Issue 23 (16th May 2013) - Miura, Hiroki; Wada, Kenji; Hosokawa, Saburo; Inoue, Masashi
Abstract The method using Ru—CeO2 is environmentally friendly due to the high recyclability of the catalyst and low contamination of the products with the metallic species.